S-Nitrosoderivative of a Recombinant Fragment of von Willebrand Factor (S-Nitroso-AR545C) Inhibits Thrombus Formation in Guinea Pig Carotid Artery Thrombosis Model - Gurevitz, Osnat; Eldar, Michael; Skutelsky, Ehud; Tamarin, Ilia; Shenkman, Boris; Eskaraev, Regina; Castel, David; Loscalzo, Joseph; Inbal, Aida (Thrombosis and Haemostasis, 2000)
Antiplatelet drugs are the mainstays of therapy for acute and chronic cardiovascular diseases. S-nitroso-AR545C – an S-nitrosoderivative of a recombinant von Willebrand factor fragment AR545C spanning Ala 444 to Asp 730 and containing an Arg 545 Cys mutation, was previously found to inhibit ristocetin-and ADP-induced platelet aggregation and the interaction of platelets with extracellular matrix (ECM). In the current study we tested the antithrombotic properties of S-nitroso-AR545C on guinea pig platelets and in a platelet-rich thrombosis model in the guinea pig. Preincubation of guinea pig platelets with 0.1 µM of S-nitroso-AR545C decreased ristocetin-induced agglutination by 40% (p = 0.009) and completely abolished ADP-induced aggregation (p <0.0001). At concentration of 1.0 µM, S-nitroso-AR545C completely inhibited platelet adhesion (represented by surface coverage – SC) and decreased aggregate formation (represented by average aggregate size – AS) by more than 50%. Treatment of guinea pigs with 1.0 mg/kg S-nitroso-AR545C resulted in a significantly delayed time to arterial occlusion (31.7 ± 6.0 min vs. 13.9 ± 3.2 min, p <0.02). Similarly, total patency time was longer in the group injected with S-nitroso-AR545C compared to the control group. However, the difference was not statistically significant (33.8 ± 6.3 min vs. 20.2 ± 3.3 min, p = 0.07). No change in platelet count, hematocrit and bleeding time was observed 60 min after injection compared to baseline. In contrast, a significant decrease in SC (p <0.0001) and AS (p <0.01) were observed 60 min after the injection of S-nitroso-AR545C, whereas no change in these parameters was observed in the control group. These observations indicate that S-nitroso-AR545C exhibits significant antiadhesive and antiaggregating effects in-vitro and inhibits clot formation in-vivo suggesting that this compound may have potential therapeutic advantages.
Keywords: von Willebrand factor; platelet inhibitors; nitric oxide